Pengaruh Fundamental Ekonomi Daerah dalam Pembangunan Ekonomi di Kota Sungai Penuh Tahun 2010-2015 - Silvia Rahayu (Universitas Batanghari Jambi, 2018)
This research has a purpose to know to know the influence of economic growth, income per capita and HDI to economic development in Sungai Penuh City either simultaneously or partially and to know how relation of bamboo handicraft production development seen from aspect of labor, raw material and capital to effort of poverty Poverty in Siulak Subdistrict Based on the results of analysis using multiple linear regression analysis obtained results: 1. Regional economic fundamentals consisting of economic growth, income per capita and HDI have a significant influence on economic development either simultaneously or partially. The amount of influence of regional economic fundamentals on economic development is as follows: a. Simultaneously, F value counted 529,104 while F table (α = 0.05; db regression = 4: db residual = 2) was 19.25. Because F arithmetic> F table is 529,104> 19,25 then regression analysis is significant. This means that H0 is rejected and H1 accepted so it can be concluded that economic development in Kota Sungai Penuh 2010-2015 can be significantly influenced by free variable of regional economic fundamentals that is economic growth variable, income per capita and HDI. B. Partially, t arithmetic X1 (economic growth) = 4.836 and t table of 2.920. Because t arithmetic> t table is 4.836> 2.920 and from the table obtained a significance value of 0.008, then the influence of X1 (economic growth) is significant. This means that H0 is rejected and H1 accepted, so it can be concluded that economic development in Kota Sungai Penuh can be significantly influenced by real economic growth variable. From the coefficient value is known that economic growth has an effect of 0.139% on economic development. T arithmetic X2 (income per capita) = 6,813 and t table is equal to 2,920. Because t arithmetic> t table is 6.813> 2.920 and from the table obtained value of significance 0.019, then the influence of X2 (income per capita) is significant. This means that H0 is rejected and H1 is accepted, so it can be concluded that economic development in Kota Sungai Penuh can be significantly influenced by per capita income variable significantly. From the coefficient value is known that income per capita have influence equal to 0,886% to economic development. T arithmetic X3 (IPM) = 6.602 and t table of 2.920. Because t arithmetic> t table is 6.602> 2.920 and from the table obtained value of significance 0.027, then the influence of X3 (HDI) is significant. This means that H0 is rejected and H1 accepted, so it can be concluded that economic development in Kota Sungai Penuh can be significantly influenced by real HDI variable. From the coefficient value is known that the HDI has an effect of 2.366% of economic development. Keywords : Economic Growth, Per Capita Income, HDI